Demographic variation in timing and intensity of feather molt in migratory Fork-tailed Flycatchers (Tyrannus s. savana) - Jahn, Alex E. [UNESP]; Giraldo, Jose I.; MacPherson, Maggie; Tuero, Diego T.; Hernan Sarasola, Jose; Cereghetti, Joaquin; Masson, Diego A.; Morales, Marvin V. (Wiley-Blackwell, 2016)
Understanding the annual cycle of migratory birds is imperative for evaluating the evolution of life-history strategies and developing effective conservation strategies. Yet, we still know little about the annual cycle of migratory birds that breed at south-temperate latitudes of South America. We aged, sexed, and determined the progression and intensity of body, remige, and rectrix molt of migratory Fork-tailed Flycatchers (Tyrannus s. savana) at breeding sites in southern South America and at wintering sites in northern South America. Molt of both body and flight feathers occurred primarily during the winter. In early winter, a similar proportion of young and adult flycatchers molted remiges and rectrices, but remige molt intensity (number of remiges molting) was greater and primary molt progression (mean primary feather molting) more advanced in adults. In late winter, remige molt intensity and primary molt progression did not differ between age groups. We found no difference between males and females either in the proportion of individuals molting in winter or in the intensity or progress of remige molt. Our results suggest that the nominate subspecies of Fork-tailed Flycatcher undergoes one complete, annual molt on the wintering grounds, and represents the first comprehensive evaluation of molt timing of a migratory New World flycatcher that overwinters in the tropics. Given that breeding, molt, and migration represent three key events in the annual cycle of migratory birds, knowledge of the timing of these events is the first step toward understanding the possible tradeoffs migratory birds face throughout the year.
Keywords: Argentina; Colombia; feather; llanos; rectrix; remige